2013
DOI: 10.2176/nmc.53.77
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Detection of Thyroid Nodules at Magnetic Resonance Imaging of the Cervical Spine

Abstract: The incidental detection of thyroid lesions in patients undergoing magnetic resonance (MR) imaging of the cervical spine was prospectively evaluated on 389 MR images. Sagittal images extended from the cranio-cervical junction to the upper thoracic level, and axial images from C3-4 to C7-T1 intervertebral levels. Twenty patients (5.1%) had a total of 26 thyroid nodules. Eighteen patients presented with a single dominant nodule, of whom 2 had a multinodular gland with a single dominant nodule (one had 3 and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…8,11 For incidental thyroid nodules found by CT and MRI, reported malignant carcinoma rates range from 3.9% to 11.3%. 7,[12][13][14] Thyroid incidentalomas on PET imaging have reported malignant carcinoma rates ranging from 13.6% to 62.5%. 9,12,15,16 Some studies have looked at thyroid incidentalomas as diagnostic dilemmas, discussing approaches for patients with an incidental thyroid lesion.…”
Section: Discussionmentioning
confidence: 99%
“…8,11 For incidental thyroid nodules found by CT and MRI, reported malignant carcinoma rates range from 3.9% to 11.3%. 7,[12][13][14] Thyroid incidentalomas on PET imaging have reported malignant carcinoma rates ranging from 13.6% to 62.5%. 9,12,15,16 Some studies have looked at thyroid incidentalomas as diagnostic dilemmas, discussing approaches for patients with an incidental thyroid lesion.…”
Section: Discussionmentioning
confidence: 99%
“…4-6 Specifically, incidentally discovered thyroid nodules (IDTNs), defined as asymptomatic nonpalpable thyroid lesions that are discovered on an imaging study unrelated to the thyroid gland, have become more prevalent. 7,8 IDTNs are reported to be present on 16% of computed tomography (CT) and magnetic resonance (MR) scans, 9,10 9% of carotid ultrasound (US), 11 and 3% of positron emission tomography (PET) scans. 12 The clinical and oncologic significance of these nodules, however, remains unclear.…”
mentioning
confidence: 99%
“…In a survey of 30 provinces and regions in China, the prevalence of thyroid nodules was reported to be as high as 36.9% in the normal population who underwent US ( 11 ). Kim et al ( 8 ) reported that the prevalence of incidental thyroid abnormalities on cervical spine MRI scans was 5.1% in their 389 participants. However, the population in their study included patients who underwent cervical spine MRI for any reason.…”
Section: Discussionmentioning
confidence: 99%
“…If the patient is aged ≥35 years, the size for further evaluation is raised to 1.5 cm, and all enlarged thyroid glands should undergo further workup with dedicated US ( 3 ). However, to date, few studies have reported the prevalence of incidental thyroid abnormalities focused on MRI, and the prevalence in cervical spine MRI in the literature ranges widely, from 5.1% to 49.6% ( 7 , 8 ). In anterior cervical surgery, vigorous mobilization of the thyroid gland, especially the development of a goiter, may damage the recurrent laryngeal nerve ( 9 ).…”
Section: Introductionmentioning
confidence: 99%